Extranodal Richter's syndrome of the urinary bladder - Almudena Carrión-Valencia; Jonathan Rodríguez-Talavera; Begoña Ballesta-Martínez (Indian Journal of Urology, 2018)
Lymphomas of the urinary bladder are rare and can be primary or secondary. The latter group includes Richter's Syndrome-which is a transformation of a chronic low-grade lymphoproliferative syndrome into a common type of non-Hodgkin lymphoma, most commonly localized in the lymph nodes. We report a case of an 84-year-old male, former-smoker with a history of low-grade chronic lymphocytic leukemia, treated with chemotherapy, with a recurrence of the disease to retroperitoneal and iliac lymph nodes, splenomegaly, and thickening of the bladder wall. The hematologist consulted us because of hematuria with coexistent bilateral obstructive uropathy. We performed transurethral resection of the bladder which revealed secondary lymphoma in the bladder, probably the result of a high-grade transformation from chronic leukemia, a very rare location of this transformation.